A Game-Based Secure Localization Algorithm for Mobile Wireless Sensor Networks. (1st September 2015) - Bao, Tianyue; Wan, Jiangwen; Yi, Kefu; Zhang, Qiang
Abstract : The issue of node localization is a fundamental problem in wireless sensor networks. Recently, the localization problem for mobile sensor networks in hostile environment has received significant attention. Due to the mobility of the sensor nodes, it is more challenging to achieve node localization in attacked sensor networks than in static ones. To address these challenges, the paper presents a novel game-based secure localization algorithm. The nodes' strategy level can be indicated through the results of trust evaluation and then by means of constructing reasonable strategy space and payoff function using game theory; all kinds of nodes within the network can achieve the optimal payoffs. The performance of our algorithm is evaluated by extensive simulation experiments. The simulation results show that the localization error of our proposed algorithm is lower than those of the existing ones in attacked environment.